2020
DOI: 10.1109/access.2020.3028097
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Lying Electrical Vehicles in Charging Coordination Using Deep Learning

Abstract: Because charging coordination is a solution for avoiding grid instability by prioritizing charging requests, electric vehicles may lie and send false data to illegally receive higher charging priorities. In this paper, we first study the impact of such attacks on both the lying and honest electric vehicles. Our evaluations indicate that lying electric vehicles have a higher chance of charging, whereas honest electric vehicles may not be able to charge or may charge late. Then, an anomaly-based detector based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Consequently, the cybersecurity aspect of the automotive has been addressed by several recent studies by authenticating the information contained in transmitted messages to thwart attackers from altering them and to check the authenticity of such information [ 30 , 31 ]. Tesla and other electric vehicles are vulnerable to attacks that send bogus State-of-Charge (SoC) information to charging stations in an effort to receive a higher charging priority [ 32 ]. Deep learning algorithms are being used in current studies to secure charging stations as well as electric automobiles [ 33 ].…”
Section: Literature Surveymentioning
confidence: 99%
“…Consequently, the cybersecurity aspect of the automotive has been addressed by several recent studies by authenticating the information contained in transmitted messages to thwart attackers from altering them and to check the authenticity of such information [ 30 , 31 ]. Tesla and other electric vehicles are vulnerable to attacks that send bogus State-of-Charge (SoC) information to charging stations in an effort to receive a higher charging priority [ 32 ]. Deep learning algorithms are being used in current studies to secure charging stations as well as electric automobiles [ 33 ].…”
Section: Literature Surveymentioning
confidence: 99%
“…Equation (6) will be used to determine how good the supplied tree structure is. Because the number of produced trees is too huge to identify the best one, a greedy approach is used to prune ineffective tree branches one level at a time, utilizing (7) to evaluate split possibilities,…”
Section: B Xgboostmentioning
confidence: 99%
“…Tesla automobiles were shown by researchers that can be hacked and they demonstrated that the crucial vehicle functions can be manipulated remotely [5]. Electric vehicles, such as Tesla, can be attacked to broadcast false state-of-charge (SoC) data to charging services in order to get greater priority for charging [7]. Current studies are not concerned only with defending electric vehicles but also protecting the charging stations using deep learning techniques [8].…”
Section: Introductionmentioning
confidence: 99%
“…The integrated learning model performed better than the supervised SVM learning. Shafee et.al [43] proposes a deep recurrent neural network based anomaly detector learning model to detect Electric Vehicles (EVs) reporting false state of change values.in a smart grid. A Non-dominated Sorting Genetic Algorithm was used to perform an exhaustive grid search.…”
Section: Literature Survey On Machine Learning (Ml) Approaches For Anomaly Detection In Smart Gridmentioning
confidence: 99%